Avaliação em hardware de modelos de consumo de energia utilizados em simuladores de redes de sensores sem fio (RSSF) - Silva, Celso Viana da (2011)
Energy consumption and, consequently, lifetime in Wireless Sensor Networks is an active field of research. In this work, we measured the current consumed by MICAz from alkaline batteries. These measurements were made through experiments with a Commercial WSN kit and an electronic circuit built with a resistor. The current consumption data obtained in the form of time series allowed the construction of several curves of the remaining capacity of alkaline batteries. Consumption was measured until MICAz stops working, determining its lifetime and its voltage-off of operation. With the voltage and current, we determined the mean energy in Joules and compared itwith the consumption of a sensor node created in the computer simulatorNS-2. The results presented in tables and comparative graphics showed that consumption ofMICAz is greater than the consumption of sensor node in NS-2.